Czech Republic : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that the Czech economy, despite its strong fundamentals, is in the midst of a prolonged recession because of the euro area slump and weak domestic demand. A further slowdown in the euro area would exacerbate the situation, creating the risk of lower growth in the long run. Short-term macroeconomic policies should therefore be geared toward supporting the economy and not creating additional drag. Boosting potential growth in the medium to long term will require implementation of additional structural reforms. Given the large fiscal consolidation achieved so far, further consolidation efforts should be avoided until the economic recovery gains strength.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet